2018
DOI: 10.1111/bjh.15557
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis unmasked by imatinib

Abstract: A 40-year-old man presented with drooping of both eyelids and generalized weakness of two weeks duration. The symptoms were worse during the evening. He had been diagnosed with chronic myeloid leukaemia (CML) in chronic phase, four months previously, and was receiving regular imatinib, 400 mg/day. After three weeks of therapy, he had achieved a complete haematological response, and his constitutional symptoms had subsided. After three months of therapy, he showed a two-log reduction of BCR-ABL1 transcript. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The reported incidence of impotence on detumescence in patients presenting late with low-flow priapism is >50%. [8] The present finding suggests that though priapism is low flow (ischemic) in CML, it has a milder phenotype and better outcome in comparison to other types of low-flow priapism.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The reported incidence of impotence on detumescence in patients presenting late with low-flow priapism is >50%. [8] The present finding suggests that though priapism is low flow (ischemic) in CML, it has a milder phenotype and better outcome in comparison to other types of low-flow priapism.…”
Section: Discussionmentioning
confidence: 47%
“…[7] The treatment modalities recommended include immediate medical management (hydroxyurea and analgesia), hydration, and TKI (imatinib) (on confirmation of CML). [8] Apart from systemic treatment, it has been described that local intracavernous therapy in the form of penile aspiration, instillation of sympathomimetic drugs such as phenylephrine, and penile shunt procedures are also beneficial in bringing down the penile swelling. [9,10] Penile biopsy is not recommended in CML with priapism.…”
Section: Discussionmentioning
confidence: 99%
“…A mediastinal mass was identified and resulted in thymic hyperplasia. The authors concluded that MG was unmasked by Imatinib, related to a disturbance of the immune function, but they could not rule out co-incidental occurrence of MG and LMC or a paraneoplastic manifestation of LMC [14]. Nevertheless, to our opinion, the presence of thymic hyperplasia should not be overlooked.…”
Section: Discussionmentioning
confidence: 78%
“…The earliest reports were of 2 CML patients who developed MG after several years of treatment with busulfan. A summary of all cases of MPNs associated with MG is presented in Table 1 [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…The authors of many reports had associated the onset of MG symptoms with the use of drugs to treat MPNs. Eg: TKI in [16], [17] and [18], busulfan in [24], [25] and [26], and interferon-alpha in [21]. However, there is no clarity in the mechanism of drug-induced MG in these reports.…”
Section: Discussionmentioning
confidence: 99%